2012
DOI: 10.1111/j.1467-9493.2012.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Competing rationalities in water conflict: Mining and the indigenous community in Chiu Chiu, El Loa Province, northern Chile

Abstract: Conflict over water is a significant phenomenon in many parts of the world where globally linked neoliberal economic activities encroach on the lands of indigenous peoples. This case study from Chile examines how water scarcity affecting indigenous agricultural communities in the Chilean Altiplano has been exacerbated by legally sanctioned mining-related practices. Notably, the legal framing of the 1981 Water Code promotes private ownership of water rights and enhanced mining activity usually at the expense of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 21 publications
0
18
0
4
Order By: Relevance
“…Moreover, water rights and uses are increasingly challenged by agents from outside the local area, which extends the conflicts to regional and even international levels (Boelens, 2011). The struggle is not simply over resources as such but also over competing rationalities and the normative constructs that define problems and hierarchies (Boelens, 2008;Camacho, 2012;McLean, 2012).…”
Section: Water-related Conflictsmentioning
confidence: 99%
“…Moreover, water rights and uses are increasingly challenged by agents from outside the local area, which extends the conflicts to regional and even international levels (Boelens, 2011). The struggle is not simply over resources as such but also over competing rationalities and the normative constructs that define problems and hierarchies (Boelens, 2008;Camacho, 2012;McLean, 2012).…”
Section: Water-related Conflictsmentioning
confidence: 99%
“…Estos actores de cambio, que por sus respuestas contrahegemónicas responden a quienes dominan la naturaleza, son el objeto de estudio de base en la Ecología Política. Las comunidades ancestrales ocupan un rol fundamental para estos fines, pues son quienes se enfrentan a los agentes del capital corporativo, cara a cara y en su propio territorio (Budds, 2004;Camacho, 2012;Prieto, 2015;Wilson & Bayón, 2017). Otro tanto acontece con los estudios de Ecología Política Urbana, donde el derecho a la ciudad y la garantía en los accesos a recursos logra caracterizar las tramas del poder y de la invención de una nueva naturaleza, inédita por su capacidad metabólica y resiliencia, como es el caso de las ciudades del Norte y Sur Global (Lawhon, Ernstson, & Silver, 2014) El desarrollo epistémico de la Ecología Política está situado, en parte, sobre el fundamento antropológico de cultura y liminalidad de la etnografía, que se ocupa del sujeto de estudio como objeto de su propio contexto.…”
Section: Launclassified
“…MEL reports that it extracted over 50,000,000 cubic metres of subterranean water from its mine in 2011 and 2012 (Minera Escondida Limitada ). As a result of the state's facilitation of corporate water extraction by CODELCO, MEL and others, and alongside the championing of the copper industry for Chile's economy, there have been numerous cases of exhaustion and pollution of aquifers by miners, to the detriment of agricultural and other use and thus the exacerbation of significant social and political inequalities in the means of life (Oyarzún and Oyarzún ; Camacho ). A handful of researchers have told the story of the failings of the Water Code in social and environmental terms for people in the north of Chile (Hendriks ; Galaz ; Yáñez and Molina ) and environmental economist, Carl Bauer (1997a, b, , ,b) and geographer, Jessica Budds (, ), have shown that there is a persistent lack of empirical evidence for the benefits of water markets in Chile and elsewhere (see also Larrain et al .…”
Section: Contested and Changing Values: Water Markets And Water Rightsmentioning
confidence: 99%